Peningkatan Kualitas SDM Dan Akses Informasi Bagi UMKM Ohoi Wain Kabupaten Maluku Tenggara - Gerrit Mathias Pentury; Novalien Carolina Lewaherilla; Saleh Tutupoho; Asiani Sijabat; Felix Chandara; Frandryo Muskita; Nurul Maghfirah (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
MSMEs have a very important role in driving the wheels of the economy. Therefore, MSME activities are economic activities that cannot be separated from people's lives in meeting the needs of life in the post-COVID-19 pandemic. Reliable MSME human resources are needed for the survival of MSMEs. This service activity aims to provide understanding and strengthening for MSME actors in the Village / Ohoi Wain, Southeast Maluku Regency about the Importance of HR Quality and Access to Information in MSME Management. It is hoped that with this Community Service activity, MSMEs will still have the motivation and maintain a survival attitude in managing their business after the COVID-19 pandemic. The method used in this activity is Counseling or Lectures for 30 MSME actors which aims to increase understanding and awareness of business actors. The result of this activity is the absorption of knowledge and skills from MSME actors through material that is understood so that MSMEs use their capacities well and try to improve their quality and competence in managing and developing MSMEs in the Village / Ohoi Wain, Southeast Maluku Regency.